ULTRA PROTECTION FOR FUTURE GENERATION WOMEN SAFETY - Elavarashi M.; Shifana M.; Gayathri K. (Galaxy International Interdisciplinary Research Journal, 2022)
The project entitled “ULTRA PROTECTION FOR FUTURE ENERATION WOMEN SAFETY”. The safety for women has turn a major issue as the day-by-day cases building up in all over the world. This proposed plan explains women’s safety and their security by using an plan to transmit alert dispatch, showing safe point & alert authorities. It suggest a stand-in view to use technology to guard women. In this scheme, an android predicated smart phone with an intertwined note that alert and provides point-predicated information. It hand nature-defence and SMS alert when a women is in trouble. Multiple cases remain mysterious due to short validation. So, unremitting showing the safe zone where, showing the victim safety tips, offline mode is a countless of the foremost useful features of this system.